Humidity and temperature monitoring - A.Abdul Wahhab, Ibtihaj; Bierk, Hussain; Ahmed Aday, Luma (International Journal of Engineering and Technology, 2019)
The prediction of climate in general and weather in particular are of paramount importance, especially with the possible negative consequences that may occur. Therefore, it is necessary to design an affordable, compacted size, and feasible weather station that provides significant information concerning humidity and temperature. In this research, we have employed a highly reliable DHT22 sensor and RF 433 hc12 for transmitting and receiving data. The DHT22 sensor is very accurate regarding humidity and temperature measurement whereas RF 433 hc12 processes high data rate, better range, and portability.This research involves a system, with low cost and high performance, to provide accurate measurement of humidity and temperature and then transmits the data to display in LCD screen.Â